Exploring How Educational Preparedness Affects the Attitudes of Nurses Regarding Sexual and Gender Minorities: A Systematic Review - Monica Nikitara; Marileni Kenteli; Evangelos Latzourakis; Costas S. Constantinou (Societies)
Numerous sources report that patients belonging to sexual or gender minority (SGM) groups often do not receive proper healthcare services due to negative attitudes from healthcare providers, including nurses. This literature review aims to explore the gaps in the existing curriculum and educational preparedness, including ehealth and mhealth trainings and how such educational preparedness affects the attitudes of nurses toward SGM groups. The search strategy included the electronic databases CINHAL, PubMed, Medline, EBSCO, and ProQuest. After reviewing and removing duplicates and irrelevant studies, 21 articles were selected to be included in this literature review. The findings of this research indicate that the provision of educational resources, including ehealth and mhealth trainings, falls short of meeting the requirements of caring for a patient who identifies with a sexual and gender minority (SGM) group. Consequently, nurses feel less confident and prepared to provide care in such situations, resulting in low comfort levels and readiness. It also reveals the nurses’ attitudes towards SGM patients affected by the lack of preparation. Key educational interventions, including targeted seminars and online modules, are recommended to enhance nurse preparedness. Implementing these interventions can foster improved attitudes and cultural competence in healthcare settings.